Heat Recovery from Composting: A Comprehensive Review of System Design, Recovery Rate, and Utilization. (15th December 2017) - Smith, Matthew M.; Aber, John D.; Rynk, Robert
ABSTRACT: It has long been recognized that composting yields a large quantity of thermal energy, which is normally lost to the surrounding environment as heat. Efforts to recover this heat using compost heat recovery systems (CHRSs) have been sporadic. Literature on the subject is also disjointed. To summarize the research that has been conducted, the authors performed an extensive literature review, covering publications in scientific journals, trade magazines, books, theses, and published reports. A focus on CHRS design and heat recovery rates is presented. The review covers 45 CHRSs in 16 different countries, ranging from simple hotbeds used in China 2000 years ago, to advanced super-thermal conductor heat pipe systems in 2016. Heat recovery rates varied significantly, with no predictable trend among the 45 systems. Recovery rates averaged 1895 kJ/hr (1159 kJ/kg DM) for lab-scale systems, 20, 035 kJ/hr (4302 kJ/kg DM) for pilot-scale systems, and 204, 907 kJ/hr (7084 kJ/kg DM) for commercial systems.